2019
DOI: 10.21315/jps2019.30.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Physical and Mechanical Properties of Steel Powder Filled Disc Brake Friction Materials

Abstract: To cite this article: Kosbe, P. E. et al. (2019). Experimental investigation of physical and mechanical properties of steel powder filled disc brake friction materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…However, for all measured samples, there was an increase in hardness compared to the base undeformed material. Increased hardness has a definite effect on the tribological properties of the measured materials, as proven by other authors [ 74 , 75 ]. The first indicator was the coefficient of friction (COF) results, which showed higher values compared to the base material.…”
Section: Discussionsupporting
confidence: 74%
“…However, for all measured samples, there was an increase in hardness compared to the base undeformed material. Increased hardness has a definite effect on the tribological properties of the measured materials, as proven by other authors [ 74 , 75 ]. The first indicator was the coefficient of friction (COF) results, which showed higher values compared to the base material.…”
Section: Discussionsupporting
confidence: 74%
“…The overall COF results point to the fact that the steels that underwent the PM production method show similar COF values with respect to the radii of rotation with the set tribological parameters and their fine-grained microstructure. The final heat treatment leads to a significant increase in hardness, which is closely related to an increase in COF values [ 38 ]. The results of the conventional steel X153CrMoV12 in the case of the base material led to a decrease in COF due to an increase in the friction temperature, which is caused by an increase in the turning radius [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Manoharan et al (2018) studied and reported that decomposition of MoS 2 occurs around 540°C to form MoO 3 with the release of sulfur dioxide, and sublimation of MoO 3 oxide occurs at about 700°C, which has affected weight loss. At the same time, it is known that at 700°C, graphite is decomposed into gases (Kosbe et al , 2019). The rest of the components, namely, wollastonite, aluminum dioxide, lead, tin, silicon dioxide and copper are not undergoing decomposition below 1,000°C.…”
Section: Resultsmentioning
confidence: 99%